2021
DOI: 10.1515/jpem-2021-0280
|View full text |Cite
|
Sign up to set email alerts
|

Children-Dietary Inflammatory Index (C-DII), cardiometabolic risk, and inflammation in adolescents: a cross-sectional study

Abstract: Objectives There is limited evidence about the inflammatory potential of diet and cardiometabolic risk in children. The aim of this study was to evaluate the association between the Children’s Dietary Inflammatory Index (C-DII) with cardiometabolic risk factors in Turkish adolescents from 10 to 17 years. Methods Participants aged 10–17 years, who completed a 24-h dietary recall, from which C-DII scores were calculated, were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The DII score of Brazilian adolescents was found to be ranged from −2.8 to 4.3 (20). Açık et al (10) found the mean cDII score in adolescents to be ranged from−3.22 to 4.09. Similarly, DII scores ranged from −4.87 (most anti-inflammatory) to 4.75 (most pro-inflammatory) in school-aged children (3).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The DII score of Brazilian adolescents was found to be ranged from −2.8 to 4.3 (20). Açık et al (10) found the mean cDII score in adolescents to be ranged from−3.22 to 4.09. Similarly, DII scores ranged from −4.87 (most anti-inflammatory) to 4.75 (most pro-inflammatory) in school-aged children (3).…”
Section: Discussionmentioning
confidence: 98%
“…The DII scores have been associated with inflammatory biomarkers, cardiometabolic risk factors, and metabolic syndrome (MetS) in adults (5). However, few studies have investigated the relationship between DII and cardiometabolic risk factors in children, and the findings were conflicted (9,10).…”
mentioning
confidence: 99%
“…There were plenty of researches exploring association between dietary inflammatory index (DII) and disease in different populations. A pro-inflammatory diet (DII>0) may be associated with an increased risk of adiposity, cardiovascular diseases or related mortality, metabolic syndrome, dementia, central nervous system demyelination, frailty, memory and cognition function impairment, and even breast cancer or thyroid cancer [8][9][10][11][12][13][14][15][16][17][18] . The DII is a comprehensive parameter of diet-derived inflammatory capacity, and designed to be universally applicable across all human studies for dietary assessment.…”
Section: Discussionmentioning
confidence: 99%
“…As women are exposed to discrimination based on gender in society, they have a fragile structure. Gender discrimination is the cause of processes such as nutrition, access to healthcare services, and being economically victims [16]. Women participate less in the labor market, and therefore, they have to live dependently.…”
Section: Discussionmentioning
confidence: 99%